Propuesta de un plan de marketing para la cooperativa de ahorro y crédito ahorrista solidario de la Ciudad De Cuenca, provincia del Azuay . - Contento Japón, Carmen Mirian (2014)
In the present study we have set targets General "Making a proposed marketing plan for the Cooperative Savers Solidario", allowing it to provide valid for the Cooperative in implementing strategies to improve your marketing skills. First materials and methods were used in the research methods applied within the Deductive Method, in this investigation it was applied in the determination of the theoretical concepts of marketing planning applicable to the Cooperative were applied, the Inductive Method, allowed to establish the reality found in the Cooperative from the particular to the general, the statistical method facilitated the tabulation of surveys of customers of the Cooperative, as well as employees and Manager of the Cooperative; within the techniques allowed to apply to a survey of customers, employees and interview the manager of the cooperative, in these conditions the data helped to formulate the strengths, weaknesses, opportunities and threats, always relying on field research in SWOT design matrix. After the external analysis were performed in the frame of the evaluation of the external factors, the sum of total weighted between opportunities and threats, it gives a value of 2.51 points; which means that on average this opportunity, thereby concludes that in this case the opportunities outweigh the threats; and therefore is defined in the external environment that 's more consistent opportunities and threats that the Cooperative should take advantage of the best way these factors are favorable for their development and internal analysis with the IFE Matrix, the Internal Factors the sum of total weighted between the strengths and weaknesses gives us a value of 2.42 points; meaning that is below the acceptable average factors, thereby conclude saying that in this case the weaknesses outweigh the strengths and therefore the Cooperative must consider this situation as the majority of the weight weaknesses significantly limited their development and sustainability, then the analysis of the Mission and Vision for staked back in the Vision, Mission, Objectives was performed. With these considerations by High Impact Matrix, five strategic objectives, among which are, at a given value of $ $ 18,533.00 raised for compliance. Finally it has come to determine the conclusions and recommendations based on the market study and proposed recommendations should be made against the implementation of the Marketing Plan.